Filaggrin Gene Mutation c.3321delA Is Associated with Various Clinical Features of Atopic Dermatitis in the Chinese Han Population - Meng, Li (Public Library of Science, 2014)
BACKGROUND: We confirmed that the filaggrin gene mutation c.3321delA is associated with atopic dermatitis in our previous genome wide association study of the Chinese Han population. c.3321delA is the most common filaggrin gene mutation in Chinese atopic dermatitis patients but is not present in European populations. OBJECTIVE: To investigate the genetic model for the c.3321delA mutation and to determine the correlation between c.3321delA and atopic dermatitis clinical phenotypes in the Chinese Han population. METHOD: The filaggrin gene mutation c.3321delA was sequenced in 1,080 atopic dermatitis patients and 908 controls from the Chinese population. The χ(2) test, ANOVA,nonparametric tests and logistic regression were used to investigate the relationship between the c.3321delA genotype and atopic dermatitis clinical phenotypes in the Chinese Han population. RESULTS: Analyses of the genetic model revealed that the additive model best described the c.3321delA mutation (P = 3.09E-11, OR = 3.43, 95%CI = 2.38–4.96). Stratified analyses showed that the c.3321delA allele frequency distribution is significantly associated with concomitant skin xerosis (P = 1.68E-03, OR = 2.13,95%CI = 1.32–3.46), palmar hyperlinearity (P = 3.64E-17, OR = 4.0,95%CI = 2.86–5.70), white dermatographism (P = 4.25E-03, OR = 1.82,95%CI = 1.22–2.71), food intolerance (P = 1.51E-03, OR = 1.76,95%CI = 1.23–2.50) and disease severity ( P = 9.67E-05). CONCLUSION: Our study indicates that the filaggrin gene mutation c.3321delA is associated with clinical phenotypes of atopic dermatitis in the Chinese Han population, which might help us gain a better understanding on the pathogenesis of atopic dermatitis.